2021
DOI: 10.3390/en14227613
|View full text |Cite
|
Sign up to set email alerts
|

Potential and Mechanisms for Stable C Storage in the Post-Mining Soils under Long-Term Study in Mitigation of Climate Change

Abstract: Carbon storage in soil increases along with remediation of post-mining soils. Despite many studies on the issue of carbon sequestration in soils, there is a knowledge gap in the potential and mechanisms of C sequestration in post-mining areas. This research, including nuclear magnetic resonance analysis, determines the soil organic carbon formation progress in a long-term study of limestone (S1), and lignite (S2) post-mining soil under different remediation stages. The main remediation target is reforesting; h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Other studies indicated an increase in alkyl-C, aromatic C, carbonyl C, and O/N-Alkyl C for remediation soil [112]. An et al [49] suggested that forest land use improves soil organic carbon quality. Our study confirmed that reforestation has a high positive influence on SOC quality as reported previously [113,114].…”
Section: Stablity Of Sequestred Socmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies indicated an increase in alkyl-C, aromatic C, carbonyl C, and O/N-Alkyl C for remediation soil [112]. An et al [49] suggested that forest land use improves soil organic carbon quality. Our study confirmed that reforestation has a high positive influence on SOC quality as reported previously [113,114].…”
Section: Stablity Of Sequestred Socmentioning
confidence: 99%
“…Therefore, O-alkyl C and carbonyl C represent the labile C fraction of SOC and show persistence for days to a year. In turn, the alkyl C and aromatic C represent the relatively stable SOC fraction with a half-life time of decades [49]. The stable C fraction mainly is deposited in soil aggregates [50].…”
Section: Introductionmentioning
confidence: 99%